Osteomyelitis Caused by Candida glabrata in the Distal Phalanx - Shunichi Toki; Naohito Hibino; Koichi Sairyo; Mitsuhiko Takahashi; Shinji Yoshioka; Masahiro Yamano; Tatsuhiko Henmi (Case Reports in Orthopedics)
Osteomyelitis caused by Candida glabrata is rare and its optimal treatment is unknown. Here we report a case of osteomyelitis caused by C. glabrata in the distal phalanx in a 54-year-old woman. Despite partial resection of the nail and administering a 1-month course of antibiotics for paronychia, the local swelling remained and an osteolytic lesion was found. C. glabrata osteomyelitis of the distal phalanx was later diagnosed after curettage. Thereafter, the patient was treated with antifungal agents for 3 months. The infection eventually resolved, and radiological healing of the osteolytic lesion was achieved. Antifungal susceptibility testing should be performed in the case of osteomyelitis caused by nonalbicans Candida species, due to their resistance to fluconazole.